Optimal distributed control problem for cubic nonlinear Schrödinger equation - Sanchez Fernandez de la Vega, Constanza Mariel (2018)
We consider an optimal internal control problem for the cubic nonlinear Schrödinger (NLS) equation on the line. We prove well-posedness of the problem and existence of an optimal control. In addition, we show first-order optimality conditions. Also, the paper includes the proof of a smoothing effect for the non-homogeneous NLS, which is necessary to obtain the existence of an optimal control.